2019
DOI: 10.17219/acem/79969
|View full text |Cite
|
Sign up to set email alerts
|

The importance of the Wnt/β-catenin pathway and LRP5 protein in bone metabolism of postmenopausal women

Abstract: Background. Postmenopausal osteoporosis is the most common metabolic bone disease among women. The Wnt signaling pathway has been known to be the critical regulator of osteoblastogenesis. Alterations in this mechanism may have consequences for bone remodeling in humans. Objectives. The aim of the study was to evaluate the frequency of genotypes and alleles of single nucleotide polymorphism (SNP) rs4988321 and rs312009 of LRP5 in Polish postmenopausal women with osteopenia (n = 109) and osteoporosis (n = 333). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…There is increasing evidence regarding the key role of the LRP5 gene in regulating bone metabolism (10,19). Here, we assessed the relationships of rs4988300 and rs634008 polymorphisms in the LRP5 gene with BTM, BMD values and fractures in a study population with SOP or osteoporotic fractures.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence regarding the key role of the LRP5 gene in regulating bone metabolism (10,19). Here, we assessed the relationships of rs4988300 and rs634008 polymorphisms in the LRP5 gene with BTM, BMD values and fractures in a study population with SOP or osteoporotic fractures.…”
Section: Discussionmentioning
confidence: 99%
“…LRP5 and β catenin are found to significantly reduce in postmenopausal osteoporosis [18]. Increased reactive oxygen species (ROS) with aging process causes osteoblast apoptosis and also decrease osteoblastogenesis by inhibiting β catenin [19]. .…”
Section: Physiology Of Aging Changes In Bonesmentioning
confidence: 99%
“…Therefore, more and more scholars are interested in the molecular mechanism between WNT signaling pathway related genes and osteoporosis. Up to now, many studies have been reported on the relationship between genetic polymorphism and susceptibility to osteoporosis (13)(14)(15)(16), but the mechanism of WNT signaling pathway in the development of osteoporosis is still unclear .…”
Section: Introductionmentioning
confidence: 99%